Pembangunan Saluran Irigasi Tersier Menggunakan Batu Kali Sebagai Upaya Peningkatan Produktivitas Pertanian - Icha Tatrisya Derka; Katminto; Adelia Nur Isna; Devi Hanurani (Universitas Jember, 2025)
Sumberwaru Village, Sukowono District, Jember is one of the areas where most of the people work in agriculture. However, the current condition of agricultural land is that there are many damaged and dry irrigation channels, while the irrigation channels themselves have an important role in increasing the efficiency of water distribution in agricultural land. Therefore, efforts need to be made to improve the irrigation system to increase agricultural productivity. The first step is to approach the community about the importance of building proper irrigation channels. This activity aims to increase community understanding and participation in the construction of irrigation channels as part of strengthening agricultural infrastructure. The method used is a community participatory approach including socialization and technical training on installing river stones, followed by evaluation. The results of the activity show that community understanding of the importance of building river stone irrigation channels has increased by 20% to 35%, both in terms of knowledge and technically. This activity is expected to be able to support community independence in developing agricultural infrastructure. In addition, increasing agricultural productivity will have an impact on increasing village food security. The evaluation results show that this activity requires costs, so it requires support from both the village government and cross-sector collaboration for the sustainability of infrastructure development on a regular basis.